Ընտանիքը որպէս «առաջին Եկեղեցի» - Պողոսյան, Իսահակ Տ․ Վրդ. (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье, ссылаясь на многочисленные цитаты из Библии и наречения святых отцов Церкви, говорится, о церковной сущности семьи в контексте Таинства Венчания. Ясно, что Божье творение рождается в рамках семьи, которая может стать храмом Божьим как в случае отдельных личностей, так и благочестивых семей. Отношения между супругами нельзя оценивать, основываясь на обмене взаимовыгодными услугами. Их следует понимать как долг, завещанный Богом. Библейские заповеди используются в основном в контексте семьи, и важная роль Церкви в Библии характеризуется прежде всего примером семьи. Таким образом, семья — это основная и предпочтительная среда, выходя из которой человек участвует в жизни общества. In the article, according to numerous testimonies of biblical and Church fathers, there is a reference (in connection with the sacrament of the Holy Matrimony) to the ecclesiastical nature and role of the family. It is clear that God’s creation is implemented within the family. Accordingly, the family has a chance to become the temple of God both in the case of individuals and in the case of godly families. Relationships between spouses should never be judged in terms of the exchange of equivalent services, but should be understood as a God-given duty. The Bible’s commandments are used primarily in the context of the family, and the important role of the Church in the Bible is characterized primarily by the example of the family. Thus, the family is the main and preferred environment, from which a person participates in the life of the society, where the security of humanity is constantly ensured.
Keywords: Քրիստոնեություն